On the Role of Core Exercises in Alleviating Muscular Fatigue Induced by Prolonged Sitting: A Scoping Review - Banafsheh Amiri; David G. Behm; Erika Zemková (Sports Medicine - Open)
Abstract Background Prolonged sitting induces fatigue in deep trunk muscles, thereby decreasing spinal support and increasing stress on the spine. Core exercises effectively facilitate recovery from trunk muscle fatigue based on evidence from subjective outcomes; however, there is a lack of systematic investigation into localized muscle activity specifically related to prolonged sitting. Therefore, this scoping review summarizes the evidence on the effects of core exercises in alleviating trunk muscular fatigue induced by prolonged sitting, focusing on objective outcomes such as electromyography (EMG) and tensiomyography. Methods Articles published between January 2010 and February 2024 were sought in PubMed, Scopus, Web of Science, MEDLINE, and Cochrane Library, as well as Elsevier, SpringerLink, and Google Scholar. The findings were reported following the guidelines provided by the PRISMA-ScR checklist. Results Out of 106 papers initially identified, eight met the inclusion criteria. During core exercises, fatigued trunk muscles exhibit an increase in EMG root mean square (RMS) values. In the post-intervention (from 9 days to 8 weeks), tensiomyography outcomes of the erector spinae muscles significantly improved, whilst EMG results were insignificant. The contraction times of both the left and right erector spinae balanced out, indicating a harmonizing effect of the exercise. Regarding the recovery of other trunk muscles, only the transversus abdominis and internal oblique muscles exhibited a significant increase in the EMG median frequency that decreased over prolonged sitting. Conclusions Core exercises are effective in alleviating muscular fatigue caused by prolonged sitting. This can be observed from significant changes in EMG and tensiomyography parameters during exercise and after the training protocol. Intervention studies have primarily targeted the recovery of the erector spinae muscles, with less attention on other trunk muscles. Although significant improvements in tensiomyography results for the erector spinae can be observed after core exercise intervention, the impact on EMG remains uncertain. Key Points 1. Core exercises have an acute effect on reducing muscle fatigue caused by prolonged sitting. 2. Core exercise intervention studies, primarily targeting the erector spinae muscles, significantly improve tensiomyography outcomes, but evidence for electromyography outcomes is lacking. In addition, few studies have analyzed the electromyography mean frequency and root mean square values, which are crucial in assessing muscle fatigue and recovery. 3. Only a few studies have investigated the effectiveness of core exercises in restoring other trunk muscles, such as the transversus abdominis and multifidus, following prolonged sitting fatigue.